Supportive care needs of patients with colorectal cancer undergoing anticancer therapy: A latent class analysis - Bei Dong; Jiyin Zhang; Fen Wang; Congyan Xie; Yishu Qi; Lu Lin; Li Tian (Elsevier, 2023)
Objective: This study was aimed at identifying the potential subgroups of supportive care needs among Chinese patients with colorectal cancer (CRC) through latent class analysis (LCA) and clarifying the characteristics of patients with high needs. Methods: From January to September 2020, a cross-sectional survey was conducted in the Oncology Department and Radiotherapy Department of four tertiary grade A hospitals in Suzhou by using the general information questionnaire and Comprehensive Needs Assessment Tool for patients with cancer. Potential subgroups of supportive care needs were identified through LCA, and the association between the subgroups and statistical variables was analyzed with chi-square tests to clarify the demographic characteristics of the high-need group. This study was not registered. Results: A total of 403 patients with CRC were included in the survey. LCA indicated two subgroups of supportive care needs in patients with CRC: a high-need group (51.86% of patients) and a low-need group (48.14% patients). In both groups, the probability of healthcare staff and information needs was high (> 50%). Single/divorced/widowed patients had greater supportive care needs than married patients, and patients with rectal cancer had greater supportive care needs than those with colon cancer. Conclusions: Patients' healthcare staff and information needs are of critical importance. Focus should be placed on unmarried, patients with rectal cancer, as well as those receiving chemotherapy plus radiotherapy or palliative treatment.